Comparison of Milligan Morgan Versus Stapled Hemorrhoidectomy in Patients Attending Tertiary Care Hospital - Muhammad Tariq Ghafoor, Syeda Sabahat Haider, Naureen Kauser, Sadaf Shahzadi, Sohail Sabir, Sajida Nasim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Hemorrhoids are common anorectal problems that cause fear by bleeding, pruritus burden, and thrombosis pain. Prolapse and hemorrhoids are managed by stapled hemorrhoidectomy (SH). Initially, Stapled hemorrhoidectomy seemed to be a good alternative for Milligan Morgan (MM) hemorrhoidectomy verified by various studies. However, recent studies found that long-term assessment of stapled hemorrhoidectomy gives poor outcomes in terms of postoperative complications and patient’s satisfaction. Therefore, the present study aimed to compare the Milligan Morgan versus stapled Hemorrhoidectomy in patients attending Tertiary Care Hospital. Methodology: This prospective study was carried out on 120 patients at the Department of Surgery Unit-I Sheikh Zayed Medical College Rahim Yar Khan from 1st May 2021 to 31th April 2022. All the patients of either gender with an age range from 18 years to 60 years after 2nd degree hemorrhoids failure of multiple rubber band ligations and 3rd and 4th degree hemorrhoids were enrolled. Concomitant anal disease patients such as ano-rectal cancer, fissure, fistula, and abscess were excluded. Patients were divided into two categories: Group-I Stapled Hemorrhoidectomy and Group-II Milligan Morgan. Post-operative complications such as stenosis and urinary retention during hospitalization were recorded. All the data were entered and analyzed using SPSS version 25. Results: The overall mean age of Group-I and Group-II was 46.78±12.66 years and 48.91±14.82 years respectively. Each group comprised 60 patients. Out of the SH group, 35 (58.3%) were males and 25 (41.7%) were females. Of the MM Group-II, male and females were 44 (73.3%) and 16 (26.7%) respectively. About 53 (88.3%) patients in Group-I and 32 (53.3%) patients in Group-II had relief from bleeding and other symptoms. The surgical duration in Group-I and Group-II was 22.9 ± 12.9 minutes and 34.8 ± 9 minutes with statistical significance (p=0.000) respectively. The vessel spurting ligation and postoperative hemorrhage was developed in 5 (8.3%) in SH group patients. Post-operative bleeding and intervention was found in 26 (43.3%) patients in Group-II. The prevalence of postoperative pain requiring analgesia was found in 20 (33.3%) in Group-I and34 (56.7%) in Group-II respectively. After treatment, fecal incontinence was developed in none of the patients in both groups. The postoperative complications such as anal tag, tenderness, bleeding, urinary retention, and wound discharge were higher in Group-II as compared to Group-I with statistical insignificance (p< 0.05). Conclusion: The present study found that hemorrhoids could be effectively treated by Stapled hemorrhoidectomy compared to Milligan-Morgan procedure in terms of postoperative pain, hospital stay, and usage of analgesics, reduced postoperative complications, patient’s satisfaction, and time taken for operation. Beside lesser complications, fecal incontinent, severe pain, and other complications could result from stapling technique. Post-operative pain and complete pain relief was significantly lower in MM group. Hospitalization in the SH group was shorter than the MM group. Hemorrhoid recurrence was null in both SH and MM group. Keywords: Hemorrhoid Surgery, Stapled Hemorrhoidectomy, Milligan-Morgan